Predictive Risk of Ulnar Collateral Ligament Injury Based on Ligament Morphology and Dynamic Abnormalities in Professional Baseball Pitchers Using Stress Ultrasonography - Mayer, Braden K. (Orthop J Sports Med, 2015)
OBJECTIVES: Ulnar collateral ligament (UCL) injury of the elbow is a common and debilitating problem seen frequently in elite baseball pitchers. Ultrasound has been shown to be a useful diagnostic tool in evaluating UCL injuries. We hypothesized that the evaluation using stress ultrasound (US) of the elbow to measure both the morphology of the UCL and the ulnohumeral joint space gapping as a surrogate for UCL incompetence will be helpful to predict UCL injury in professional baseball pitchers. METHODS: Ultrasound imaging was used to assess the medial joint laxity of both arms of 70 asymptomatic professional baseball pitchers during spring training. Medial joint laxity and UCL morphology was assessed using OsiriX Imaging Software under 2 conditions: (1) gravity valgus load and (2) 10 lbs of valgus load using a handheld dynamometer with the shoulder in the maximal cocking position and the elbow in 90° of flexion. Two trials of resting position, elbow gapping, and UCL thickness were collected, measured and averaged for data analysis. Intra and inter rater reliability was established and maintained with ICC's in the acceptable range for all measures (.84-.99). One-way ANOVA (α=0.05) was used to compare pitchers’ dominant variables between those with a prospective UCL injury to those who never had a UCL injury. Receiver Operating Curve (ROC) was used to identify pitchers who, based on elbow gapping measures (by cut score), were at high-risk versus those at low risk for UCL injury. (AUC > .70; α=0.05). RESULTS: Players with a prospective UCL injury (n=7) presented with a trend toward wider (mm) D arm resting joint opening (4.9± 1.2 vs. 4.0±1.1; p=0.07), significantly wider gapped opening (6.5± 1.2 vs. 5.3 ± 1.2; p=0.01) and greater peak stiffness (nm) (.17±.09 vs. 10 ±.07; p=0.03) when compared to pitchers without UCL injury history (n=63). Figure 1 displays larger values of dynamic elbow gapping differentiated between UCL injured (>5.5 mm) and uninjured pitchers (AUC=0.77; p=0.02). CONCLUSION: Our data suggests that changes present in the UCL and detectable on ultrasound may help distinguish elbows at risk for later clinical UCL insufficiency. Screening using ultrasound of UCL thickness, loaded joint gapping, and stiffness may help predict the likelihood of elbow injury in professional baseball pitchers.